2016
DOI: 10.1155/2016/7450461
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling in Patients with Upper Tract Urothelial Carcinoma Associated with Balkan Endemic Nephropathy

Abstract: Balkan endemic nephropathy (BEN) is a disease that affects people that live in the alluvial plains along the tributaries of the Danube River in the Balkan region. BEN is a chronic tubulointerstitial disease with a slow progression to terminal renal failure and has strong association with upper tract urothelial carcinoma (UTUC). There are several hypotheses about the etiology of BEN, but only the toxic effect of aristolochic acid has been confirmed as a risk factor in the occurrence of the disease. Aberrantly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 55 publications
(54 reference statements)
1
21
0
Order By: Relevance
“…Generally, Aristolochia and one of its chief components aristolochic acid have been known for its carcinogenic, and nephrotoxic effects for a very long time ( Michael et al., 2009 ). Recently, several toxicological risks associated with a history of using herbal medicines containing aristolochic acid amongst cancer patients have been reported ( Aydin et al., 2017 ; Ban et al., 2018 ; Chen et al., 2018 ; Hoang et al., 2016 ; Hung et al., 2016 ; Kanaan et al., 2016 ; Popovska-Jankovic et al., 2016 ; Xiong et al., 2018 ; Zhong et al., 2017 ). Despite the reported cases on the use of herbs containing aristolochic acid around the world, a similar effect associated with the use of Aristolochia spp has yet to be reported in Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, Aristolochia and one of its chief components aristolochic acid have been known for its carcinogenic, and nephrotoxic effects for a very long time ( Michael et al., 2009 ). Recently, several toxicological risks associated with a history of using herbal medicines containing aristolochic acid amongst cancer patients have been reported ( Aydin et al., 2017 ; Ban et al., 2018 ; Chen et al., 2018 ; Hoang et al., 2016 ; Hung et al., 2016 ; Kanaan et al., 2016 ; Popovska-Jankovic et al., 2016 ; Xiong et al., 2018 ; Zhong et al., 2017 ). Despite the reported cases on the use of herbs containing aristolochic acid around the world, a similar effect associated with the use of Aristolochia spp has yet to be reported in Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Tao et al [47] reported a serum signature comprising 10 miRNAs to potentially distinguish UTUC from healthy patients with hematuria, and Zaravinos et al [48] analyzed miRNA expression profiles to distinguish renal cell carcinoma and UTUC samples from each other and from healthy tissue. One study focused on biological pathways affected by differential miRNA expression [49], and two studies particularly analyzed miRNAs involved in AAinduced UTUC [50,51]. It is noteworthy that AA-induced UTUC was reported to harbor different miRNA signatures compared with sporadic UTUC.…”
Section: 3mentioning
confidence: 99%
“…In recent years, more than 30 microRNAs differentially expressed in patients exposed to AAs have been explored, which might improve the understanding of the pathogenesis of AA-related renal disease and cancer. It has been speculated that FGFR3, Akt, mucin type O-glycan biosynthesis, ECM receptor interaction pathways, and other biological mechanisms might be involved in the occurrences of AAN, BEN, and/or AA-induced UTUC (Tao et al, 2015; Lv et al, 2016; Popovska-Jankovic et al, 2016). Meanwhile, 15% of the 417 detectable miRNAs have been found to be altered by AAs in rats (Li et al, 2015).…”
Section: Toxicological Properties Of Aristolochic Acidsmentioning
confidence: 99%